Eleanor Marx and Shakespeare. (3rd April 2018) - Holmes, Rachel
ABSTRACT: This essay explores the importance of Shakespeare to the immediate family and friendship circle of Karl Marx and especially to his youngest and only British-born daughter and literary heir. It relates Shakespeare as instrumental to Eleanor Marx's discovery of drama, feminism and concepts of Englishness in particular.